2011
DOI: 10.1098/rsfs.2010.0034
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts and synergies in different biofuel reports

Abstract: The societal debate on biofuels is characterised by increased complexity. This can hinder the effective governance of the field. This paper attempts a quantitative bird's eye meta-analysis of this complexity by mapping different stakeholder perspectives and expected outcomes as seen in the secondary literature on biofuels, along the lines of the People-Planet-Profit framework. Our analysis illustrates the tension between stated and actual drivers of large scale biofuel development, especially for first generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…For example, the authors noticed that industrial SMEs focused more on the economic side and converted all their perspectives to equivalent dollars in their discussions. This observation is consistent with the results of a previous study that indicated that business personnel and private sector personnel tend to highlight the importance of profit and the financial side more in their evaluations (Michalopoulos et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, the authors noticed that industrial SMEs focused more on the economic side and converted all their perspectives to equivalent dollars in their discussions. This observation is consistent with the results of a previous study that indicated that business personnel and private sector personnel tend to highlight the importance of profit and the financial side more in their evaluations (Michalopoulos et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Stakeholders' requirements include notes on the capital risks of investing in biofuels (Wright, Brown, & Boateng, 2008) and facility size requirements (Jack, 2009). Stakeholders generally support biofuel development when there is a clear opportunity for profit (Michalopoulos, Landeweerd, Werf-Kulichova, Puylaert, & Osseweijer, 2011). The work that addresses environmental requirements focuses primarily on CO 2 and greenhouse gases (GHG) emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The workshop was preceded by an analysis of issues in biofuel reports published by various stakeholders (eg the Food and Agricultural Organization, The World Bank, Worldwatch, the International Energy Agency, Greenpeace, Friends of the Earth), 19 which revealed uncertainty among scientific experts and other stakeholder clusters, as different reports presented different facts and figures, and highlighted different societal, legal and ethical issues. 20 The Centre also organised two public debates held in The Netherlands during September 2008 to identify issues of concern to the public. 21 The first debate, organised in Amsterdam, was aimed at defining sustainability criteria.…”
Section: First Steps To Integrate Societal Issues In Industrial Innovmentioning
confidence: 99%
“…Stakeholders' requirements include notes on the capital risks of investing in biofuels (Wright, Brown, & Boateng, 2008) and facility size requirements (Jack, 2009). Stakeholders generally support biofuel development when there is a clear opportunity for profit (Michalopoulos, Landeweerd, Werf-Kulichova, Puylaert, & Osseweijer, 2011). The work that addresses environmental requirements focuses primarily on CO 2 and GHG emissions.…”
Section: Literature Reviewmentioning
confidence: 99%